A new species of pincer wasps of Deinodryinus Perkins (Hymenoptera, Dryinidae) from oceanic archipelago of Fernando de Noronha, Brazil - André Luis Martins (Papéis Avulsos de Zoologia, 2022)
Abstract The first record of the genus Deinodryinus Perkins and the description of a new species Deinodryinus noronhensis sp. nov. from oceanic archipelago of Fernando de Noronha (Brazil) are performed. Additionally, an illustration of the new species and a modified key are presented together with a discussion on the Deinodryinus records for the northeastern region of Brazil.